AB0077 Leptin is Related with Inflammation and Metabolic Syndrome Features and Resistin with Disease Severity in Patients with Psoriasis Undergoing Treatment with Adalimumab. (9th June 2015) - Pina Murcia, T.; Genre, F.; Lopez-Mejias, R.; Armesto, S.; Ubilla, B.; Mijares, V.; Dierssen-Sotos, T.; Corrales, A.; Gonzalez-Lopez, M.; Gonzalez-Vela, M.D.C.; Blanco, R.; Llorca, J.; et al.
Abstract : Background: Altered secretion patterns of proinflammatory adipokines may influence the increased risk of cardiovascular disease observed in patients with chronic inflammatory diseases. Objectives: To determine whether two adipokines, leptin and resistin, correlate with metabolic syndrome features and disease severity in patients with psoriaisis. Methods: Prospective study of consecutive non-diabetic patients with moderate-to-severe psoriasis who completed 6 months of therapy with adalimumab. Patients with kidney disease, hypertension or body mass index ≥35 kg/m 2 were excluded. Metabolic and clinical evaluation was performed at the onset of treatment and at month 6. Results: 29 patients were assessed. A correlation between adiposity (waist circumference) and leptin was observed after 6 months of therapy: r=0.43; p=0.030. Leptin also correlated with blood pressure before therapy (systolic: r=0.48; p=0.013. Diastolic blood pressure: r=0.50; p 0.010). A marginally significant negative correlation between insulin sensitivity (QUICKI) and leptin levels was also observed. CRP levels correlated with leptin prior to the onset of adalimumab (r=0.45; p=0.020) and with resistin both before (r=0.45; p=0.020) and after six months of therapy (r=0.55; p=0.004). A positive association between parameters of disease activity such as BSA (r=0.60; p=0.001) and PASI (r=0.63; p=0.001) and resistin concentrations prior to the onset of adalimumab therapy was also disclosed. No significant changes in leptin and resistin concentrations before and after six month adalimumab treatment were seen. Conclusions: In patients with moderate-to-severe psoriasis leptin correlates with metabolic syndrome and inflammation whereas resistin is associated with inflammation and disease severity. Acknowledgements: Abbvie Inc. funded this study Disclosure of Interest: None declared